Propuesta de sistema gerencial integral para el Hospital Dr. Aníbal González Álava de Calceta - Bravo Loor, Rubia Patricia (2016)
The objective of this research was to propose a management system to strengthen the administration of the hospital Dr. Aníbal González Calceta Alava, for the development of this study, a literature review in books and magazines on models of integrated management was conducted in order to build the framework, then information was raised by an assessment of the managerial approach of the institution to which an interview was applied to the hospital director, also were surveyed the medical and administrative staff, they are tabulated the results of the investigation to define the elements necessary for the preparation of the proposed comprehensive management, as conclusions functions and activities for the evaluation of the position he plays the director of the institution, he showed that hospital management does not meet all the administrative processes identified because there are failures when executing the various functions, the necessary elements for the design of integrated management system in order to prepare the proposal was socialized with the staff and director of the Hospital Dr. Anibal Gonzalez Alava Calceta defined.